The Association of Omega-3 Fatty Acids and Cardiovascular Outcomes in Patients with Acute Coronary Syndrome. - Ortiz, Ronnie. (2017)
Abstract: Cardioprotective associations have been seen with omega-3 fatty acids, specifically the omega-3 index which is the sum of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) fatty acid fractions inside the red blood cell and to a lesser extent with serum omega-3 fatty acid levels. However, the association of omega-3 fatty acids in acute coronary syndromes (ACS) is less established. We conducted a retrospective cohort study of patients with ACS who participated in the biological mechanism cohort of the IMMEDIATE Trial. We first examined the relationship of omega-3 index on the composite outcome of cardiac arrest, or mortality or hospitalization for heart failure within 30 days. Second we looked at the relationship of omega-3 index and 30-day infarct size. Third, we evaluated the effects GIK has on changes in EPA and DHA fractions in the serum over the 12 hour treatment period. Fourth, using the initial blood sample, we checked the correlation of the summed EPA plus DHA fractions in the serum and with the corresponding summed fractions from the red blood cell (omega-3 index). Using survival analysis, there was no significant association between the omega-3 index and our composite outcomes at 30-days (HR 0.78, 95% CI 0.48-1.26). Spearman's Rank correlation test showed no association between omega-3 index and infarct size, rho=0.02, p=0.82. The use of GIK, compared to placebo, was associated with significantly higher mean serum EPA at the first two evaluation periods of infusion (initial: p<0.01, 6 hours: p<0.01, 12 hours: p=0.06). Mean serum DHA was higher in GIK versus placebo at all time points, but failed to reach significance at an adjusted alpha of 0.017 (initial: p=0.35, 6 hours: p=0.03, 12 hours: p=0.38). A positive correlation was found between the sum of serum EPA plus DHA with omega-3 index, rho 0.50, p<0.01. Among participants with ACS the omega-3 index was not significantly associated with our composite outcome. GIK had a significant effect on changes over time in serum EPA but not on DHA. There was a significant correlation between summed EPA and DHA fractions measured in the serum and in the omega-3 index.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Harry Selker.; Committee: Harry Selker, Joni Beshansky, and Robin Ruthazer.; Keywords: Medicine, Public health, and Nutrition.